2019
DOI: 10.2298/vsp170328029s
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with depression in the patients with diabetes mellitus type 2

Abstract: Background/Aim. The assessment of association of depression and diabetes mellitus type 2 using the Patient Health Questionaire (PHQ-9) has not been done in Montenegro. The aim of this study was to assess the prevalence of depression in the patients with type 2 diabetes mellitus, and to identify the risk factors associated with the presence of depression. Methods. A cross-sectional study was conducted at the General Hospital in Bijelo Polje, from July to September, 2015. It included 70 patients over 35 years of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The same cutoff point was identified from studies conducted elsewhere. 17 Good glycemic control: Average fasting blood glucose level from three recent visits of ≤130 mg/dL was considered good glycemic control. Poor glycemic control: an average of three recent visits fasting blood glucose level of >130 mg/dL was deemed to be poor glycemic control.…”
Section: Operational Definitionmentioning
confidence: 99%
See 2 more Smart Citations
“…The same cutoff point was identified from studies conducted elsewhere. 17 Good glycemic control: Average fasting blood glucose level from three recent visits of ≤130 mg/dL was considered good glycemic control. Poor glycemic control: an average of three recent visits fasting blood glucose level of >130 mg/dL was deemed to be poor glycemic control.…”
Section: Operational Definitionmentioning
confidence: 99%
“…Our study finding is smaller than study reports conducted at Addis Ababa, Ethiopia (44.7%), 22 Saudi Arabia (49.6%), 30 Karachi, Pakistan (43.5%), 10 Malaysia (40.3%), 15 Nepal (40.3%) 31 and Montenegro (62.9%). 17 This may partly be due to the difference in socio-demographic characteristics, 30 small sample size, 2,14 study period and outcome variable measurement methods 10,15,30,31 of study subjects.…”
Section: Magnitude Of Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…"A Trinidad study reported a prevalence of 17.9% among subjects with type 2 diabetes" [15]. In a study done in Nigeria, the prevalence of depression among T2DM was 30% [16] while in Bangladesh, a prevalence of 34% was reported [17]. "It was reported by the World Health Study, that the prevalence of depression in diabetes was 2% in adults aged 18 years and above, in 60 different countries over the period of one year" [18].…”
Section: Introductionmentioning
confidence: 99%